The Determination of Nutrient Intake on Productivity and Potential Methane Emission of Fat-Tailed Sheep Fed Odot Grass as a Source of Crude Fibre - Luthfi, N.; Solkhan, M.; Suryani, Hasna Fajar; Hindratiningrum, N. (Jurnal Sain Peternakan Indonesia, 2023)
The purposes of this study were to examine the determination of crude protein (CP), Crude Fibre (Cfi) and total digestible nutrients (TDN) on the productivity and potential methane emission of fat-tailed sheep (FTS) fed Odot grass (Pennisetum purpureum cv. Mott) as a source of crude fibre. The materials used were 15 male FTS with an initial body weight (BW) of 19.5 kg ± 0.61 (CV = 0.59). The feed consisted of 28.57% Odot grass, 14.29% coffee peel, 4.28% rice bran, 7.86% pollard, 21.43% cassava, 21.43% corn cobs and 2% molasses. Sheep were reared intensively in pens for 30 days. Feed and water were provided ad libitum. The parameters in this study were dry matter intake (DMI), CP intake, Cfi intake, TDN, FTS productivity, and the determination of nutrient intake on FTS productivity and methane output. The data were analysed using correlation regression analysis. The results showed that the DMI was 956.67 g/day, CP intake was 119.31 g/day, Cfi intake was 256,22 g/day, TDN intake was 634.54 g/day, ADG 102,03 g/day and FCR of 10.1 g feed/g ADG. The potential methane emission of FTS-fed Odot grass as a source of fibre was 59.49 litres/day. DMI, CP and TDN positively correlate with methane emission (r=0.77). Cfi intake consumption is very closely related to methane output (r=1). Based on the results of the study, to increase FTS ADGs of 100 g required DM 4.76% BW, CP requirement was 120.8 g/100 gADG and TDN requirement was 642.4 g/100gADG, Cfi requirement was 259.40g/100gADG with methane emission of 60.26 litres.